Effect of Connection Detailing on Reverse Cyclic Behaviour of Precast Beam to Column Grouted Cementitious Billet Connections - Noor Ul Ameen MAHAMOOD UL HASAN; Ramamurthy VIDJEAPRIYA (Medžiagotyra)
In reinforced concrete framed structures exposed to high lateral loads, the performance of the beam to column joints has been acknowledged to have a significant impact on the overall behaviour of the structures. The present study conducted an experimental investigation on four 1/3rd scale Precast Concrete (PC) beam-to-column grouted cementitious billet connections subjected to reverse cyclic loading. Their performance was compared with a reference monolithic connection. The various precast connections studied are Billet with Dowel (BD) connection, Billet with Dowel-cleat Angle (BD-CL) connection, and Extended Billet with Dowel-cleat Angle (EBD-CL) connection. The ultimate load-carrying capacity, ductility factor, hysteretic behaviour, load ratio, energy dissipation, and stiffness degradation of the monolithic (MO) and precast (PC) specimens were studied, and a comparison of their performances was made. The results show that the EBD-CL connection has comparable ductility and strength.